Encountering grasslands: a collective approach to urban biodiversity - Walsh, Chloe; Allan, Penny (Frontiers in Sustainable Cities, 2023)
While the prolific nature of many grass and herbaceous species in urban parks offers an opportunity to cultivate more biodiverse and dynamic grasslands, widespread maintenance practices and complex cultural, economic, and bureaucratic forces often result in the undervaluing and regular destruction of these plant species. The research described in this paper reimagines the way grassy landscapes are cared for and understood in urban environments. Located in an urban park in inner Sydney, Australia, and using design research methods of observation, physical care, storytelling and installation, the research proposes three “frames of care” to assist landscape architects and other spatial designers to engage with communities at a local level. The frames have the potential to expand collective understandings of grassland communities, test alternative maintenance practices, and better support urban biodiversity and seasonal flux. With acknowledgment to the complexities of urban sites such as these, experimental installation provided a promising space to meaningfully engage with the local community and build a foundation to generate greater reciprocity between humans and non-humans of the site.